Garun Valeevich Yusupov and His Contribution to the Study of Epigraphy and Archaeology of the Volga-Ural Region (in honor of the 110th birthday of the scientist) - Albert T. Akhatov (Археология евразийских степей)
The article is dedicated to the 110th anniversary of the birth of the renowned scholar Garun Valeevich Yusupov, who made significant contributions to the study of ethnography, epigraphy, and archaeology of the Volga-Ural region, as well as to the preservation of epigraphic heritage in the area. The author examines the key stages of G.V. Yusupov's life and his research interests, which primarily focused on epigraphic and archaeological monuments. Garun Valeevich's scholarly career was closely tied to two major academic institutions in the Volga-Ural region—the Institute of Language, Literature, and History of the Kazan Branch of the USSR Academy of Sciences (1948–1952, 1958–1968) and the Institute of History, Language, and Literature of the Bashkir Branch of the USSR Academy of Sciences (1952–1958). If during his studies and work at the Institute of Language, Literature, and History, G.V. Yusupov established himself as a talented epigraphist, it was at the Institute of History, Language, and Literature that Garun Valeevich developed into a professional archaeologist. The writing of this work drew on documents and materials from the Academic Archive of the Ufa Federal Research Center RAS, which shed light on the understudied period of the scholar's work at the Institute of History, Language, and Literature. The archive contains his personal file, expedition reports from various years, and other materials. The scholarly legacy of G.V. Yusupov, comprising several dozen publications and records of studied epigraphic and archaeological monuments, remains relevant today and is used in research on ethnogenetic and ethnocultural processes that took place in the Volga-Ural region during the Iron Age, the Middle Ages, and the Modern Era.